Somatic embryogenesis and regeneration of polianthes tuberosa L. / Sakinah binti Abdullah - Abdullah, Sakinah (2012)
An efficient protocol was developed for rapid propagation and regeneration of the Polianthes tuberosa L. plantlets via somatic embryogenesis pathway using leaf, stem and flower bud as explants. Explants were cultured on MS media supplemented with various combinations and concentrations of BAP and NAA to induce callus formation. Leaf explants cultured on MS media supplemented with 2.0 mg/l NAA was the best to produce optimum callus. Within 5 months the percentage of explant produce callus was 100.00 ± 0.00%. Stem explants started to produce callus earlier (4 weeks) than other explants. 100.0±0.00 % of stem explant produced callus in MS media supplemented with 2.0 mg/l NAA, MS media supplemented with 3.0 mg/l NAA and MS media supplemented with 0.5 mg/l BAP in combination with 2.0 mg/l NAA. Flower bud explants was suitable when cultured on MS media supplemented with 2.0 mg/l NAA and MS media supplemented with 0.5 mg/l BAP in combination with 2.0 mg/l NAA. All the explants (100.0±0.00 %) produced callus. Green and white creamy in colour and soft watery structure of callus from leaf explant were then identified whether it is embryogenic or non embryogenic callus using double staining method. Embryogenic callus was stained in red and non embryogenic callus was stained in blue. Embryogenic callus was then subculture onto solid and liquid somatic embryos induction media. MS media supplemented with 2,4-D at concentration 2.5 mg/l combine with 0.1 mg/l BAP is the best media, where an average of 26.67±0.42 somatic embryos was obtained from 0.5 cm of embryogenic callus from liquid media and 20.53±0.50 somatic embryos was form on solid media. Globular, heart shape, torpedo and cotyledonary stage of somatic embryos were observed in this media. Somatic embryos were then transferred to regeneration media. A combination of 2.0 mg/l Kin with 2.0 mg/l NAA yield the best shoot regeneration from somatic embryos, producing 26.23±0.74 number of microshoot. MS media supplemented with 0.5 mg/l Kin and 2.0 mg/l NAA is the most suitable media for root formation with 4.23±0.40 number of roots formation. Complete plantlets were then transferred to greenhouse. Plantlets response positively when acclimatized in garden soil (combination of black soil and red soil at ratio 2 to 1) with 63.33±0.09 % of survival rate.